Revolusi Pendidikan Etika Akuntan Indonesia: Membuktikan Spirit Pendidikan Tan Malaka - Habib Muhammad Shahib (UNSIKA (Universitas Singaperbangsa Karawang), 2016)
The Ethics issue is one of the accountant global problems, including the accountant in Indonesia. Allegedly, the basic problem of why ethics issues always happened is based on the accountant education process. This paper is trying to examine an alternative education model based on Tan Malaka’s educational perspective that have a basis in the real situations of Indonesians and stand with the Indonesians’ interests. Hopefully, by using Tan Malaka’s educational perspective, it can deliver a new model of ethics education in accounting field and the ethical accountants in the future. Especially, the accountants that stand with the nation and Indonesians interests.